2007
DOI: 10.1002/yea.1471
|View full text |Cite
|
Sign up to set email alerts
|

A new putative Zygosaccharomyces yeast species isolated from traditional balsamic vinegar

Abstract: The taxonomic status and species number of the genus Zygosaccharomyces have rapidly changed in the last years. In this study, two new osmotolerant Zygosaccharomyces strains isolated from traditional balsamic vinegar, viz. ABT301 and ABT601, were investigated to elucidate their taxonomic relationships with Zygosaccharomyces rouxii species. A multi-gene sequence approach was employed, including regions of the rDNA repeat [5.8S, two internal transcribed spacers (ITS) and the 26S D1/D2 domain], COX2 mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 39 publications
4
42
0
Order By: Relevance
“…nov. in relevant genome-level properties. These results were also confirmed by phylogenetic divergences among these strains, previously demonstrated using the mitochondrial cytochrome oxidase II gene (COX2) and two nuclear housekeeping markers (imidazole-glycerol-phosphate dehydratase, HIS3, and Na + / H + -antiporter, ZrSOD2, respectively) (Solieri et al, 2007).…”
Section: Genetic Diversity Sequence Analyses and Species Delineationsupporting
confidence: 78%
See 3 more Smart Citations
“…nov. in relevant genome-level properties. These results were also confirmed by phylogenetic divergences among these strains, previously demonstrated using the mitochondrial cytochrome oxidase II gene (COX2) and two nuclear housekeeping markers (imidazole-glycerol-phosphate dehydratase, HIS3, and Na + / H + -antiporter, ZrSOD2, respectively) (Solieri et al, 2007).…”
Section: Genetic Diversity Sequence Analyses and Species Delineationsupporting
confidence: 78%
“…The ITS domain sequencing of strains ABT301 T and ABT601 revealed that three non-orthologous ITS sequences (arbitrarily referred to as copies 1-3) coexisted within the genome of a single strain (Solieri et al, 2007), whereas two ITS sequences were found from strain ATCC 42981 (Gordon & Wolfe, 2008). An increasing number of examples have been recently reported on intragenomic polymorphism in ITS sequences within the same strain of fungal and yeast species (Wang & Yao, 2005;Fell et al, 2007;Kageyama et al, 2007;Jacques et al, 2009;Connell et al, 2010;Saksinchai et al, 2012).…”
Section: Genetic Diversity Sequence Analyses and Species Delineationmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine yeast species were identified, but only Z. rouxii and D. hansenii were directly identified by 5.8S rRNA gene RFLP; for the other species the sequencing of the D1/D2 domain of the 26S rRNA gene was necessary, because atypical restriction profiles of 5.8S-ITS were registered. An atypical polymorphism for this region is not surprising, since many authors observed this behaviour in several yeasts (Solieri et al, 2007;Tofalo et al, 2009). The two osmotolerant Z. mellis and Z. rouxii are commonly associated with the honey environment (Deak, 2007;Carvalho et al, 2006), but no previous detection of A. pullulans, C. uzbekistanensis and D. hansenii in honey sources are available in literature.…”
Section: Discussionmentioning
confidence: 85%